The Value of Mathematical Modeling in Teaching Econometrics to Students of Higher Educational Institutions (Eurasian Research Bulletin, 2023)
This article contains the researcher's comments on the importance, necessity and relevance of using mathematical models in teaching econometrics to students of higher educational institutions. The scientific article contains opinions that the model, modeling, mathematical model and mathematical modeling are the advantages of the science of econometrics and the need to use a mathematical model when building an econometric model.